Leptin is key to peroxynitrite-mediated oxidative stress and Kupffer cell activation in experimental nonalcoholic steatohepatitis - Chatterjee, Saurabh (2012)
BACKGROUND AND AIMS: Progression from steatosis to steatohepatitic lesions is hypothesized to require a second hit. These lesions have been associated with increased oxidative stress, often ascribed to high levels of leptin and other proinflammatory mediators. Here we have examined the role of leptin in inducing oxidative stress and Kupffer cell activation in CCl(4)-mediated steatohepatitic lesions of obese mice. METHODS: Male C57BL/6 mice fed with a high fat diet (60%kcal) at 16 weeks were administered CCl(4) to induce steatohepatitic lesions. Approaches included use of immuno-spin trapping for measuring free radical stress, gene-deficient mice for leptin, p47 phox, iNOS and adoptive transfer of leptin primed macrophages in vivo. RESULTS: Diet-induced obese (DIO) mice, treated with CCl(4) increased serum leptin levels. Oxidative stress was significantly elevated in DIO mice liver but not in OB/OB mice, or in DIO mice treated with leptin antibody. In OB/OB mice, leptin supplementation restored markers of free radical generation. Markers of free radical formation were significantly decreased by the peroxynitrite decomposition catalyst FeTPPS, the iNOS inhibitor 1400W, the NADPH oxidase inhibitor apocynin, or in iNOS or p47 phox-deficient mice. These results correlated with the decreased expression of TNF-alpha and MCP-1. Kupffer cell depletion eliminated oxidative stress and inflammation, whereas in macrophage-depleted mice, the adoptive transfer of leptin-primed macrophages significantly restored inflammation. CONCLUSIONS: These results, for the first time, suggest that leptin action in macrophages of steatotic liver through induction of iNOS and NADPH oxidase caused peroxynitrite-mediated oxidative stress thus activating Kupffer cells.